Evaluation of open hernioplasty in bilateral inguinal hernia repair - Gamal Al-Shemy; Ahmed Hassan; Abd Al-Kareem Elias; Ali Nagi (Wolters Kluwer Medknow Publications, 2018)
Background Inguinal hernia occurs in ∼1.5% of the general population and in 5% of male individuals. The bilateral type affects about 12% of patients, the direct and the combined ones being more frequent than the indirect. Simultaneous or sequential repair has been debated especially after tension-free repairs. Aim This study was carried out to compare Stoppa procedure with bilateral Lichtenstein hernioplasty for the treatment of primary bilateral inguinal hernia. Patients and methods This trial included 80 male patients with primary bilateral inguinal hernias. They were divided randomly into two equal groups. Group A underwent bilateral Lichtenstein hernioplasty and group B underwent Stoppa repair. Preoperative, operative, and postoperative characteristics were recorded for each patient in the study. Patients were followed up at 3, 6, and 12 months postoperatively. Results As regards preoperative data, there was no statistically significant difference between both groups. The Stoppa operation took a significantly shorter time than the bilateral Lichtenstein technique; the mean operative time for Stoppa and bilateral Lichtenstein was 84.0±8.6 and 96.4±6.2 min, respectively. Visual analogue scoring of pain 12 h postoperatively was significantly lower in the Stoppa group than in the bilateral Lichtenstein group. As regards operative and postoperative complications, there was no significant difference between both groups. Hospital stay, return to normal daily activities, and inguinodynia rates were similar in both groups. There was no recorded recurrence in both groups up to 1 year of follow-up. Conclusion Bilateral primary inguinal hernias can be operated upon in one setting without an increase in morbidity or recurrence rate. The Stoppa technique can be a good alternative to bilateral Lichtenstein procedure for the treatment of bilateral inguinal hernia, with comparable outcome.